Efektivitas Asap Cair Kayu Rambutan dalam Menghambat Pertumbuhan Colletotrichum sp Secara In Vitro - Mahmud, Yusmar; Sulaiman, Mulky; Ikhsan Zam, Syukria (Journal of Comprehensive Science, 2024)
Leaf blight is one of the main diseases in oil palm nurseries, as a result of the attack of the pathogen Colletotrichum sp. The initial symptoms are found on the edges of the leaves. Colletotrichum sp. is a pathogenic fungus that causes blight in oil palm, so it needs to be controlled. One of the alternative controls is by using rambutan wood liquid smoke. This study aims to obtain an effective concentration of rambutan wood liquid smoke that can inhibit the growth of Colletotrichum sp. in vitro. This research was carried out from November 2023 to January 2024 at the Laboratory of Pathology, Entomology, Microbiology and Soil Science, Faculty of Agriculture and Animal Husbandry, Sultan Syarif Kasim State Islamic University, Riau. This study used an experimental method with a complete randomized design (RAL) with 6 treatments (0%, 1%, 2%, 3%, 4% and 5%) with each treatment repeated 4 times, so that there were 24 experimental units. Observation parameters include total phenol analysis and PH test of liquid smoke, macroscopic, growth rate (cm/day) and inhibition (%) Colletotrichum sp. The results showed a total phenol content of 3.47% and a PH test. Rambutan wood liquid smoke with a concentration of 4% is very effective in inhibiting Colletotrichum sp. 100% inhibition and growth rate of 0 cm/day.